E-Module Development of Sustainable Coffee Processing to Improve Vocational Students’ Green Skills - Mustika Nuramalia Handayani; Muhammad Oka Ramadhan; Shinta Maharani; Dewi Cakrawati; Mukhidin Mukhidin (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aimed to analyze the eligibility of e-module and the effectiveness of their use in improving the green skills of vocational students. This research used development research using the ADDIE model (analysis, design, development, implementation, and evaluation). The components of green skills studied in this study include knowledge of the impact of coffee processing on the environment, waste management, and sustainable coffee processing innovations. Data collection was carried out through validation sheets distributed to validators to determine the feasibility of the e-module. In addition, test questions were used in this study to determine the effectiveness of the e-module in improving students' green skills. Furthermore, the data were analyzed using the N-gain test. The results showed that the E-module was eligible according to material experts, learning media experts, and linguists. In addition, the e-module is quite effective in improving vocational students' green skills. The results of this study indicate that the integration of the concept of sustainable coffee processing into learning media is the right decision for improving the green skills of vocational students